2010
DOI: 10.1111/j.1365-4632.2009.04366.x
|View full text |Cite|
|
Sign up to set email alerts
|

Subcutaneous cysticercosis diagnosed by mitochondrial DNA analysis

Abstract: When characteristic morphology is absent in histopathology specimen, mitochondrial DNA diagnosis is a powerful tool for a definitive diagnosis of cysticercosis. The DNA diagnosis using such histopathologic specimens would also be applicable for identification of other parasites as extensive DNA sequence data are currently available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Primers targeting large subunit rRNA gene were selected to identify and amplify degraded DNA in degenerated and calcified cysts/lesions as Dalmasso et al (2004) have shown that degraded DNA can still be amplified by PCR if primers are designed to amplify a shorter target sequence, between 100 and 300 bp. Human neurocysticercosis from brain biopsy tissues (Harrington et al 2009), subcutaneous cysticercosis from histopathological specimens (Shih et al 2010) and bovine cysticercosis in postmortem inspection samples (Chiesa et al 2010) were confirmed by targeting cytochrome c oxidase subunit 1 (Cox1) gene. Lino Junior (2004) also reported the importance of PCR test with TBR primers as a reliable method for detection of cysticerci in tissues from human autopsies that are in advanced evolutive stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers targeting large subunit rRNA gene were selected to identify and amplify degraded DNA in degenerated and calcified cysts/lesions as Dalmasso et al (2004) have shown that degraded DNA can still be amplified by PCR if primers are designed to amplify a shorter target sequence, between 100 and 300 bp. Human neurocysticercosis from brain biopsy tissues (Harrington et al 2009), subcutaneous cysticercosis from histopathological specimens (Shih et al 2010) and bovine cysticercosis in postmortem inspection samples (Chiesa et al 2010) were confirmed by targeting cytochrome c oxidase subunit 1 (Cox1) gene. Lino Junior (2004) also reported the importance of PCR test with TBR primers as a reliable method for detection of cysticerci in tissues from human autopsies that are in advanced evolutive stages.…”
Section: Discussionmentioning
confidence: 99%
“…genomic DNA (gDNA) in dubious cysts, suspected lesions or cyst residues from pig and cattle in the slaughterhouse situation (Gonzalez et al 2006;Geysen et al 2007;Chiesa et al 2010). Polymerase chain reaction (PCR) test was also used in the diagnosis of cysticerci of T. solium from tissues of humans (Harrington et al 2009;Shih et al 2010). Therefore, in the present study PCR test was employed for the specific detection of T. solium cysts in suspected lesions and also for validation of meat inspection results, so that it could be developed as an appropriate postmortem test for validation of traditional meat inspection results.…”
Section: Introductionmentioning
confidence: 99%
“…Neurocysti-cercosis (Space-occupying, cystic intracranial lesions, epilepsy) PCR [138,139] Nested PCR [140] Semi-nested PCR [141] PCR amplified DNA sequences targeting T. solium mitochondrial cox1 gene and cob gene [142] Loop-mediated isothermal amplification [143] II B [147]. Histoplasma capsulatum antigen and antibodies can be determined by different methods in CSF and are used to establish diagnosis.…”
Section: Cysticercus Cellulosaementioning
confidence: 99%
“…Table lists the CNS helminthoses, their neurological manifestation, and the modern molecular‐based diagnostic techniques. It needs to be stressed even more that in helminthic diseases, the direct visualization or detection of the helminths, either the adult worm, the larval stage, or the eggs, be it in body fluids or biopsied material, still represents the golden standard of diagnosis.…”
Section: Parasitesmentioning
confidence: 99%